Potential benefits of Moringa peregrina defatted seed: Effect of processing on nutritional and anti-nutritional properties, antioxidant capacity, in vitro digestibility of protein and starch, and inhibition of α-glucosidase and α-amylase enzymes - Sardabi F; Azizi MH; Gavlighi HA; Rashidinejad A (Elsevier Ltd, 2022)
This study aimed to eliminate the bitter taste of Moringa peregrina press cake (MPC) as a byproduct of oil extraction (by employing safe and conventional methods) and evaluating its potential for formulating value-added food products. The characteristics (nutritional and anti-nutritional properties, monosaccharide composition, in vitro starch and protein digestibility, antioxidant capacity, and in vitro α-glucosidase, and α-amylase inhibitory activity) of raw, debittered (soaked in distilled water and boiled), and roasted (after debitterization) MPC flours were determined. Debitterization significantly increased total protein, fiber, arabinose, xylose, antioxidant activity, in vitro protein digestibility, and α-amylase inhibitory activity, whereas it decreased total starch, resistant starch, starch digestibility, ash, glucose, phytic acid, tannin, and oxalate contents. Fiber content, protein digestibility, α-amylase inhibitory activity, and antioxidant activity were further increased as the result of roasting. MPC and its products could inhibit α-amylase activity, with the highest inhibition belonging to roasted debittered samples. The current study is the first to report on the comprehensive nutritional and bio- and physicochemical aspects of Moringa peregrina press cake and the effect of treatments on improving its sensorial, nutritional, and health-promoting properties. Therefore, these results indicate the potential of treated MPC as a novel natural functional ingredient for various food formulations.
Keywords: Moringa peregrina; α-Amylase inhibitory; Antioxidant activity; Debitterization treatment; Roasting; Anti-nutritional properties